Analysis of Students’ Understanding of Environmental Pollution: Perception, Attitude and Awareness of Students towards Environment in Sidoarjo - Sholikhah, Ulfiyatus; Shofiyah, Noly (Journal of Research and Educational Research Evaluation, 2024)
This study aims to describe the level of students' understanding of environmental pollution, describe the level of perception, attitude, and awareness of students towards environmental pollution, and describe the relationship between variables (perception, attitude, and awareness) that affect students' understanding of environmental pollution. Quantitative non-experimental research using a survey method that uses comprehension test questions and questionnaires as the main instruments. The instruments used were test questions on students' environmental understanding of environmental pollution and questionnaires on students' perceptions, attitudes, and environmental awareness of environmental pollution. The population amounted to 9 schools out of 191 using a random sampling technique and 500 samples of grade IX students. Based on the results, the level of students' understanding of environmental pollution was found to be good. The level of perception, attitude, and awareness of students towards environmental pollution is obtained by very good criteria. Each variable has a positive influence with the variable that has the greatest influence is the influence of awareness on attitudes with a value of 0.194 with a value of P≥0.05, so the significant value has a positive influence.